Direction of Regulating Catcall Actions in Law: Comparison of Indonesia and France Law - Halim, Evelyne Julian (Lex Scientia Law Review, 2021)
Various forms of harassment in the world are increasing, including in Indonesia. Women and children are the most frequent victims of sexual harassment, but it does not rule out that men can become victims. Catcalling is an act that has sexual implications for the victim with teasing, whistling, screaming, comments, and even eye contact on the street or in public places. Sexual harassment negatively impacts victims such as shame, offense, humiliation, anger, loss of self-esteem, loss of chastity, depression, etc. Writing this scientific article aims to provide reference material for lawmakers regarding the ideal regulation of street harassment, especially catcalling. Then, give the readers an understanding of catcalling and the urgency of its rule in Indonesian legislation. The research method used in this scientific article is a normative juridical method with data collection techniques using literature study by examining secondary data, namely statutory regulations, other legal documents, research results, assessment results, and other references. This study uses a statute approach, conceptual approach, and comparative approach. This verbal sexual harassment has been taken seriously in several countries, one of which is France. In France, this anti-catcalling Law is known as Loi Schiappa. Loi Schiappa gave direct fines to the perpetrators of catcalling. In Indonesia, there is no regulation regarding catcalling, resulting in a legal vacuum. Indonesia can follow the model of the French Catcalling arrangement, which uses direct fines on the spot. So that provides legal certainty as well as protects the human rights of victims of catcalling.